INSTITUTIONAL OWNERSHIP AND AGENCY CONFLICT CONTROLLING MECHANISM - Wardhana, Leo Indra; Tandelilin, Eduardus (Journal of Indonesian Economy and Business, 2011)
The research investigates ownership structure in Indonesia in context of agency theoryÂ for non-financial firms listed on the Indonesian Stock Exchange for 2000-2007 periods.The uniqueness of characteristic of ownership structure in Indonesia, which is dominatedÂ by large institutional shareholders motivated researcher to examine the impact and itsÂ relationship to agency conflict and balancing off agency theory in Indonesian companies.In this condition, it is certainly indicating that the existing conflict is not betweenÂ managers and owners but majority and minority.Â The study argues that in low level ownership, controlling institutional shareholderÂ expropriates the minority shareholders. However, when the ownerships comes to higherÂ level, the controlling shareholder will make agency conflict lower since monitoringÂ hypothesis becoming relevant in such level. In other words, the study argues that nonlinearÂ relation between agency conflict which is proxied by firmâs performance ratios andÂ controlling institutional ownership exist. Nevertheless, the study argues that debt andÂ dividend policy can also be used to reduce the conflict. Thus, the study also examines theÂ simultaneous relationships among the mechanisms used to reduce agency conflict.The result indicates that when controlling institutional shareholder has significantÂ amount of shares, they will actively monitor the manager to ensure them making value.However, when the ownership is insignificant, controlling shareholder will harm firmÂ value due to expropriation of controlling shareholder. Therefore, nonlinear relationshipexists between controlling institutional shareholder and agency conflict. Second, debtÂ policy and dividend policy can be used to reduce the conflict. The last, it is found thatbalancing off agency theory is not applied among all policies. The only bidirectionalÂ relationship is between institutional ownership and debt policy.Keywords: controlling institutional ownership, agency theory, balancing off agencyÂ theory, debt policy, dividend policy